2010
DOI: 10.5539/ijps.v2n1p107
|View full text |Cite
|
Sign up to set email alerts
|

Well - Being Therapy (WBT) for Depression

Abstract: In clinical psychology, Well-Being Therapy (WBT) is a relatively modern technique of managing patients with depression. Well Being Therapy is based on Ryff's multidimensional model of psychological well-being. Fava has developed and validated it in a number of randomized controlled trials. The findings indicate that positive evaluation of one's self, sense of continued growth and development is possible by specific intervention. The objective of this therapy is to increase the level of psychological well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…With regard to the depression scores in the control group, it can be concluded that changes in the level of depression in the experimental groups are the direct effect of principals of cognitive behavioral therapy. These results are comparable to previous studies on different populations in Iran which reported a significant reduction in participants' depression scores as a result of group or individual CBT (Moeenizadeh, 2010;Abolghasemi, 2008;Nilforooshan et al, 2006;Forozande, 2002) in Iran.…”
Section: Discussionsupporting
confidence: 81%
“…With regard to the depression scores in the control group, it can be concluded that changes in the level of depression in the experimental groups are the direct effect of principals of cognitive behavioral therapy. These results are comparable to previous studies on different populations in Iran which reported a significant reduction in participants' depression scores as a result of group or individual CBT (Moeenizadeh, 2010;Abolghasemi, 2008;Nilforooshan et al, 2006;Forozande, 2002) in Iran.…”
Section: Discussionsupporting
confidence: 81%
“…In the last two sessions, therapists review the patient's progress and clinical state, they stress the importance of adjusting the dimensions of psychological well-being to an individualized optimal balance in line with client's changing needs (Ruini & Fava, 2012), and they provide guidance how to prevent future relapse. Research on the efficacy of WBT in treating affective and anxiety disorders has been robust (Fava et al, 2002;Fava et al, 2005;Fava et al, 2004;Moeenizadeh & Salagame, 2010;Ruini & Fava, 2009). Furthermore, a modified WBT protocol (Child-WBT, CWBT) that combines CBT sessions with sequential WBT sessions has been implemented in a group of children reporting emotional and behavioral disorders, with promising results (Albieri et al, 2009).…”
Section: Examples Of Evidence-based Clinical Positive Psychology Intementioning
confidence: 99%
“…Psychological well-being refers to how an individual is able to develop his potential and abilities optimally, as individuals who function physically, emotionally and psychologically (Ryff, 1995). Psychological well-being in individuals is not only described as a condition where there is no mental disorder that occurs in an individual, but also how the individual is aware of the psychological resources that exist within and implement it (Huppert, 2009;Moeenizadeh & Salagame, 2010). Employee well-being is very important in the quality of customer service interactions (Clarke & Rao Hill, 2012).…”
Section: Psychological Well-beingmentioning
confidence: 99%